Synthesis and characterization of polyaniline- polypyrrole composite - Abdolahi, Ahmad (Trans Tech Pub, 2014)
The current paper aims to study on synthesis of polyaniline (PANI)-polypyrrole (PPY) composite through simple interfacial polymerization method using chloroform as organic solvent, ammonium persulphate as an oxidant agent and sulphuric acid as a dopant. The composite was characterized by using Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and four pint probe methods. FESEM results showed the formation of fibrous PANI-PPY composite. FTIR and XRD results confirmed the successful formation of PANI-PPY composite. Four-point probe results showed the low electrical conductivity of the product. This study gives the better understanding on synthesis and characterization of the PANI-PPY through simple interfacial polymerization method.